A descriptive study of the startup ecosystem of the Philippines - Estonina, Chinna Baleriado (University of the Philippines Diliman, 2014)
Philippines is considerably the fastest growing economy in Asia and has fairly gained and increase competitive advantages on its macroeconomic environment, financial services and in doing business. The government is pleased with the result of its fiscal reforms which prove their commitment to improve the nation's credibility and stability in the international scene. As part of the commitment of the Philippine government, innovation shall be pursued and seen as an essential factor in harnessing culture of competitiveness. The Philippines promotes the role of technological innovation and business venture to have a positive impact on its economic growth. Entrepreneurial culture will be fostered among Filipinos by encouraging them to invest in their own businesses and become successful and innovative entrepreneurs. To enable to understand where the Philippines lies in the global competitiveness in terms of innovation and business environment, this study focuses on displaying the information and attempts to criticize the elements involving its startup ecosystem. Many investors' eyes are seeing Philippine grounds where dense, potential market exists and good investment can prosper. The market is relatively big, large segments have not yet been tapped and starting up a business is easier than in the previous years. The different components of the startup ecosystem are complete from the pool of talents, entrepreneurs, investors, VCs, incubators, backed up with education and training facilities, infrastructure and government policies. But how these players interact to each other, what needs to be created and developed, how to go through the vicious cycle of ideation to incubation to customary exits are some of the vital activities that were looked into. The visibility and support from its prospective investors and funders to develop and shape the startup ecosystem of the Philippines coupled with risk-taker, social, would-be entrepreneurs seeking capital is promising but there are works to be done. This study encourages technopreneurship and the essence and role of entrepreneurs and innovation in driving the economy forward. Inspired by the workings around Silicon Valley, an indomitable mother of all startups, the Philippines is gaining key learning in the areas of setting up startup companies. The country is in the early stage of development on its own startup ecosystem. It presents a lot of opportunities that every Filipino can grab first with the right elements - skills, funds, idea and the market. It is just a matter of time when this cycle will be showcasing prime technological innovations and run by local creative and entrepreneurial minds of the young and talented Filipinos.